2019
DOI: 10.1088/1361-6439/ab4dfc
|View full text |Cite
|
Sign up to set email alerts
|

Multimode excitations for complex multifunctional logic device

Abstract: The simplicity and prospect of energy efficiency of microelectromechanical systems (MEMS) resonatorbased computing devices have captivated considerable research interest in recent years. Hence, they are being explored for ultralow power computing machines, which are currently needed for internetofthings (IoT) applications. Recently, there have been successful demonstrations of fundamental logic gates. However, the realization of complex multifunctional logic devices that involve multiinput and multioutput line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The in-plane micro-electromechanical portal frame (U-shape) structure has the advantage of being of multi-input and multi-output device, which can be utilized for applications in sensing, signal filtering, logic, and energy harvesting 7 , 28 , 29 . Its multi-channel feature can provide various tunability options with different ports/electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…The in-plane micro-electromechanical portal frame (U-shape) structure has the advantage of being of multi-input and multi-output device, which can be utilized for applications in sensing, signal filtering, logic, and energy harvesting 7 , 28 , 29 . Its multi-channel feature can provide various tunability options with different ports/electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…multimode excitation [30], and linear and nonlinear frequency modulations [19]. A low actuation voltage and high isolation RF MEMS switches were investigated in [31] by controlling the axial stresses in microbeams to induce desirable buckling and bending effects.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated the importance of proper modeling with analytical and numerical techniques to understand their complex behavior. At the micro-scale, U-shaped structures are very common for in-plane operations, such as electrothermal actuation [50], and logics [51]; as well as for out-of-plane operations, such as energy harvesting [52], and other linear and static applications.…”
Section: Introductionmentioning
confidence: 99%